2019
DOI: 10.2134/jeq2018.05.0216
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Multifunctionality of Integrated Buffer Zones in Northwestern Europe

Abstract: Abbreviations: DK, locations in Denmark; DM, dry matter; GB, locations in Great Britain; HRT, hydraulic residence time; IBZ, integrated buffer zone; ICP-OES, inductively coupled plasma optical emission spectroscopy; SE, locations in Sweden; SRP, soluble reactive phosphorus; TN, total nitrogen; TP, total phosphorus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
(80 reference statements)
0
37
0
Order By: Relevance
“…Transient storage was approximately four times larger with watercress present compared with the same reach without the plants. N uptake rates by roots [6] were equivalent to 1.43 mg N/g shoot DM/d in summer (water temperature = 13 • C) and 0.52 mg N/g shoot DM/d in winter (water temperature = 10 • C). P uptake rate was 0.20 mg P/g shoot DM/d in summer.…”
Section: Comparison With Other Work On Nutrient Retention By Macrophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Transient storage was approximately four times larger with watercress present compared with the same reach without the plants. N uptake rates by roots [6] were equivalent to 1.43 mg N/g shoot DM/d in summer (water temperature = 13 • C) and 0.52 mg N/g shoot DM/d in winter (water temperature = 10 • C). P uptake rate was 0.20 mg P/g shoot DM/d in summer.…”
Section: Comparison With Other Work On Nutrient Retention By Macrophytesmentioning
confidence: 99%
“…However, check-dams can be used to manage steeper sites and offer the advantage of promoting settling of sediment in pockets along the ditch length. Danish integrated buffer zones (IBZs) have shown NO 3 -N removal rates of 0.3-0.5 g N/m 2 /d with efficiencies decreasing from 80% to 20% as N loads increased from 1 to 4 g N/m 2 /day, but very variable and even negative P removal efficiencies occur [6].…”
Section: Comparison With Other Work On Nutrient Retention By Macrophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that narrow riparian buffer zones (i.e., 3 m) with various management regimes (without additional measures) were insufficient to protect streams from excess nutrients. Zak et al (2019) discussed designs of integrated buffer zones (IBZs) across northwestern Europe that aim to improve nutrient retention efficiencies in smaller buffer widths. The incorporation of structural elements of mini‐wetlands and trees gave an average NO 3 removal efficiency of 23 to 37% and an average total P removal efficiency of 18 to 52%.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
“…There is an implicit assumption of the delivery of ecosystem services related to riparian buffer functions, but considerable uncertainty in evidence remains as to how to achieve and assess these (Stutter et al, 2012). Several papers in this collection show that appropriate management of riparian buffers can enhance the delivery of multiple ecosystem services (Brown et al, 2019; Dal Ferro et al, 2019; Hille et al, 2019; Singh et al, 2019; Zak et al, 2019), along with improving the ecological value of the riparian zones and the adjacent aquatic habitat. Zak et al (2019) showed that IBZ designs, encompassing tree and mini‐wetland areas in relatively narrow margins, can act as a habitat for a diverse range of species, including species of conservation concern.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%